COMPARISON OF CYTOPATHOLOGICAL SAMPLES COLLECTED IN BASIC HEALTH UNITS AND PRIVATE CLINICS IN THE MIDWEST OF SANTA CATARINA - Dallazem, Barbara; Dambrós, Bibiana Paula; Gamba, Conrado de Oliveira; Perazzoli, Marcelo; Kirschnick, Alexandre (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
OBJECTIVE: To compare the quality of cervicovaginal samples obtained from basic health units of the SUS and private clinics to screen precursor lesions of cervical cancer. METHODS: It was an intervention study whose investigated variables were: adequacy of the samples; presence of epithelia in the samples; and the cytopathological results. A total of 940 forms containing biological samples were analyzed: 470 forms for women attended at basic health units of the SUS and 470 examined in private clinics in January and February 2016. RESULTS: All unsatisfactory samples were collected at basic health units and corresponded to 4% of the total in this sector (p<0.0001). There was a higher percentage of samples containing only squamous cells in the SUS (43.9%). There was JEC representativity in 82.1% of the samples collected in the private service (p<0.0001). Regarding negative results for intraepithelial lesions and/or malignancies, the percentages obtained were 95.9% and 99.1% (p<0.0049) in the exams collected in the private system and SUS, respectively. Less serious lesions corresponded to 0.89% of the samples from SUS and 2.56% of the tests from the private sector; as concerns more serious lesions, they were not represented in the samples obtained from basic health units, whereas the percentage was 1.49% in private institutions. CONCLUSION: There is a need for guidance and training of professionals who perform this procedure to achieve higher reliability in the results and more safety for women who undergo this preventive test. Keywords: Cervix Uteri. Biological Specimen Banks. Neoplasia. Unified Health System. In-Service Training.